2011
DOI: 10.1186/1472-6963-11-37
|View full text |Cite
|
Sign up to set email alerts
|

The validity of using ICD-9 codes and pharmacy records to identify patients with chronic obstructive pulmonary disease

Abstract: BackgroundAdministrative data is often used to identify patients with chronic obstructive pulmonary disease (COPD), yet the validity of this approach is unclear. We sought to develop a predictive model utilizing administrative data to accurately identify patients with COPD.MethodsSequential logistic regression models were constructed using 9573 patients with postbronchodilator spirometry at two Veterans Affairs medical centers (2003-2007). COPD was defined as: 1) FEV1/FVC <0.70, and 2) FEV1/FVC < lower limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 44 publications
4
96
0
Order By: Relevance
“…Our method of using the ICD-9-CM code to identify COPD has been previously shown to have diagnostic accuracy. 49 Furthermore, our baseline mean SGRQ-TS of 46 Ϯ 15 is strikingly similar to the baseline mean SGRQ-TS of 46 Ϯ 17 in UPLIFT, 49 Ϯ 17 in TORCH, and 50 Ϯ 20 in the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) study, arguing against any signifi cant error in the COPD diagnosis. 34,36,50 We did not ascertain information about acute exacerbations prior to study entry that may impact HRQL and daily step counts.…”
Section: Discussionsupporting
confidence: 62%
“…Our method of using the ICD-9-CM code to identify COPD has been previously shown to have diagnostic accuracy. 49 Furthermore, our baseline mean SGRQ-TS of 46 Ϯ 15 is strikingly similar to the baseline mean SGRQ-TS of 46 Ϯ 17 in UPLIFT, 49 Ϯ 17 in TORCH, and 50 Ϯ 20 in the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) study, arguing against any signifi cant error in the COPD diagnosis. 34,36,50 We did not ascertain information about acute exacerbations prior to study entry that may impact HRQL and daily step counts.…”
Section: Discussionsupporting
confidence: 62%
“…This increased the captured diagnosis specificity as shown in previous work in other chronic diseases as hypertension 18,41 and chronic obstructive pulmonary disease. 42 Lastly, we were able to capture the high-dose steroid filling, but we cannot ensure that the intention for the prescribed drug was for acute exacerbation of UC. Other diseases are treated with oral corticosteroids, such as rheumatoid arthritis and systemic lupus.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies the exposure (COPD) and outcome (VTE) were defined according to International Classification of Diseases codes and treatment with COPD medications. Previous studies have reported low validity of COPD diagnoses obtained from administrative databases [15,16]. Similarly, a validation of VTE diagnoses in the Danish National Patient Registry reported positive predictive values for VTE diagnoses from emergency departments and hospitals of 44% and 67-77%, respectively [17].…”
Section: Introductionmentioning
confidence: 96%